Piping material, piping structure, and method for manufacturing piping material

The piping material with a specific composition and design addresses the issue of reduced compressive strength in thermally expandable graphite-containing pipes by enhancing fire resistance and structural integrity, effectively blocking fire-related smoke and heat.

JP7619767B2Active Publication Date: 2025-01-22SEKISUI CHEMICAL CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2020082170
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-09
Filing Date
2020-05-07
Publication Date
2025-01-22
Estimated Expiration
2040-05-07

AI Technical Summary

Technical Problem

Piping materials containing thermally expandable graphite suffer from reduced compressive strength and are prone to damage, especially when a coating layer is present, compromising their fire resistance.

Method used

A piping material with a tubular peripheral wall composed of 100 parts by mass of thermoplastic resin and 4 to 10 parts by mass of thermally expandable graphite, having a specific outer diameter, aspect ratio, and compression ratio, along with a coating layer that ensures a fusion strength of 1.5 MPa or more, and a refractory layer with controlled thickness and thermal conductivity.

Benefits of technology

The piping material exhibits enhanced fire resistance and resistance to damage, maintaining structural integrity during fire conditions while effectively preventing the rise of flames, heat, and smoke through compartment penetrations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619767000004
    Figure 0007619767000004
  • Figure 0007619767000005
    Figure 0007619767000005
  • Figure 0007619767000006
    Figure 0007619767000006
Patent Text Reader

Abstract

To provide a piping material excellent in fire resistance and hard to be damaged.SOLUTION: A piping material comprises a tubular peripheral wall. The peripheral wall has a tubular refractory layer containing 100 pts.mass of a thermoplastic resin and 3 pts.mass or more and 20 pts.mass or less of scaly heat-expandable graphite, where a compression ratio measured based on a flatness test specified in JIS K 6741:2016 is 20% or more. It is preferable to provide a coating layer that is located on at least one of the inner peripheral surface and the outer peripheral surface of the refractory layer and covers the refractory layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a piping material to be installed inside a building such as an apartment building, a piping structure, and a method for manufacturing the piping material. [Background technology]

[0002] In buildings such as apartment buildings, adjacent upper and lower floors are separated by a floor slab, and on each floor, two adjacent rooms are separated by a wall to form a compartment. A piping structure for draining or supplying water is installed inside the building, and through holes (in this specification, these through holes are referred to as compartment through holes) are formed in the floor slab and wall through which the piping structure passes. An example of a piping structure passed through the partition penetration part of the floor slab is one that includes a first standpipe (piping material) installed vertically on the lower floor relative to the floor slab, a second standpipe (piping material) installed vertically on the upper floor relative to the floor slab, a horizontal branch pipe (piping material) installed above the floor slab, and a three-way pipe joint provided with a socket for connecting each pipe. In such a piping structure, the upper end of the first standpipe is connected to the socket of the pipe joint in the partition penetration part formed in the floor slab. In addition, a sealing material such as mortar is filled between the inner surface of the partition penetration part and the pipe joint to fill the gap between the inner surface of the partition penetration part and the pipe joint.

[0003] In order to prevent flames, heat, and smoke from rising from a floor where a fire has broken out to upper floors through compartment penetrations, piping structures are usually provided with fire-resistance measures to block flames, heat, and smoke at compartment penetrations in the event of a fire. The Fire Service Act and Building Standards Act require that piping that penetrates a compartment with fire-resistance measures (fire compartments) also be fire-resistant.

[0004] As a fireproofing measure for a piping structure, a method is known in which the piping material inserted into the compartment penetration portion contains thermally expandable graphite. For example, a piping material has been proposed that has a fire-resistant layer containing a specific amount of thermally expandable graphite with a specific expansion temperature, and a coating layer located on the inner and outer peripheral surfaces of the fire-resistant layer (Patent Document 1). According to the invention of Patent Document 1, when a fire breaks out and heat rises, the heat causes the piping material to expand and block the compartment penetration. This makes it possible to prevent flames, heat, and smoke from rising through the compartment penetration. In addition, a single-layer or multi-layer piping material having a tubular fire-resistant layer made of a fire-resistant resin composition containing a specific amount of thermally expandable graphite and a specific amount of zinc phosphate has been proposed (Patent Document 2). According to the invention of Patent Document 2, further improvement in fire resistance has been achieved. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4960806 [Patent Document 2] JP 2018-54045 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when the fire-resistant layer contains thermally expandable graphite, the compressive strength of the piping material is reduced, making the piping material more susceptible to breakage. This problem is more pronounced when the fire-resistant layer has a coating layer on at least one of the inner and outer circumferential surfaces. SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a piping material that is excellent in fire resistance and is resistant to breakage. [Means for solving the problem]

[0007] The present invention has the following aspects. <1> A tubular peripheral wall is provided, The peripheral wall is made of 100 parts by mass of a thermoplastic resin, heat Expandable graphite 4 parts by mass or more 10 Mass part less than and a tubular fireproof layer containing The outer diameter is 165 mm or more and 318 mm or less, The following measurement method The measured compression rate is 20% or more. the law of nature, The average aspect ratio of the thermally expandable graphite is 10 or more and 35 or less. Piping materials. <Measurement method> A ring-shaped test piece of 50 mm or more is cut from the pipe material and left at 23°C for one hour, after which the pipe is sandwiched between two flat plates and the outer diameter of the pipe is compressed perpendicular to the pipe axis at a speed of 10 mm / min. The degree of radial compression at the time of destruction is measured for three ring-shaped test pieces, and the average value is taken as the compression ratio. <2> A tubular peripheral wall is provided, The peripheral wall is made of 100 parts by mass of a thermoplastic resin, heat Expandable graphite 4 parts by mass or more 10 Mass part less than and a tubular fireproof layer containing The outer diameter is 76 mm or more and 140 mm or less, The thickness of the fireproof layer is 70% or less of the thickness of the peripheral wall, The following measurement method The measured compression rate is 20% or more. the law of nature, The average aspect ratio of the thermally expandable graphite is 10 or more and 35 or less. Piping materials. <Measurement method> A ring-shaped test piece of 50 mm or more is cut from the pipe material and left at 23°C for one hour, after which the pipe is sandwiched between two flat plates and the outer diameter of the pipe is compressed perpendicular to the pipe axis at a speed of 10 mm / min. The degree of radial compression at the time of destruction is measured for three ring-shaped test pieces, and the average value is taken as the compression ratio. < 3 >A coating layer is provided which is located on at least one of the inner and outer circumferential surfaces of the fire-resistant layer and covers the fire-resistant layer, <1> or <2> The piping material described in < 4 The fusion strength between the fire-resistant layer and the coating layer is 1.5 MPa or more. 3 >Piping materials described in. < 5 The fire-resistant layer has a weld line extending in the tube axis direction, <1> ~< 4 > Piping material described in any one of the above. < 6 The thermal conductivity of the peripheral wall is 0.3 W / m K or less. <1> ~< 5 > Piping material described in any one of the above. < 7 The fire-resistant layer contains a flame retardant. <1> ~< 6 > Piping material described in any one of the above.

[0008] < 8 > <1> ~<7 A piping structure in which the piping material according to any one of the above items is pre-joined with an upper pipe joint and a lower pipe joint, The upper pipe joint has a connection portion that is connected to an upper end of the piping material, The lower pipe joint has a connection portion that is connected to a lower end of the piping material, A piping structure, in which, when the piping structure is installed, at least the piping material is positioned within a compartment penetration portion of a floor slab, and the piping material protrudes downward from the floor slab.

[0009] < 9 A multi-layer structure having at least a tubular fire-resistant layer and an inner coating layer located on the inner peripheral surface of the fire-resistant layer. 3 > or < 4 A method for producing a piping material according to the above. The inner coating layer comprises a polyvinyl chloride resin, The fire-resistant layer is made of polyvinyl chloride resin. The heat and expandable graphite, The fire-resistant layer and the inner coating layer are laminated and extruded using an extrusion die, and then the laminate is introduced into a sizing sleeve to shape the outer surface. Effect of the Invention

[0010] The piping material of the present invention has excellent fire resistance and is resistant to breakage. [Brief description of the drawings]

[0011] [Figure 1] 1 is a cross-sectional view showing one embodiment of a piping structure of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a manufacturing apparatus for manufacturing a piping material with a three-layer structure. [Diagram 3] 3 is a cross-sectional view showing an example of a mold provided in the manufacturing apparatus of FIG. 2. [Figure 4] FIG. 4 is an end view of the mold of FIG. [Diagram 5] FIG. 3 is a schematic diagram showing an example of a vacuum sizing device provided in the manufacturing apparatus of FIG. 2. [Figure 6]FIG. 1(a) is a partial cross-sectional view showing an example of the state of the end of a piping material (pipe) inserted into a receiving port of a pipe fitting, and FIG. 1(b) is a partial cross-sectional view showing another example of the state of the end of a piping material (pipe) inserted into a receiving port of a pipe fitting. [Figure 7] 2 is a cross-sectional view showing a state in which a fire breaks out in a building in the piping structure of FIG. 1. FIG. [Figure 8] FIG. 4 is a cross-sectional view showing another embodiment of the piping structure of the present invention. [Figure 9] FIG. 4 is a cross-sectional view showing another embodiment of the piping structure of the present invention. [Figure 10] FIG. 2 is a cross-sectional view showing a universal testing machine used in the evaluation of the examples and comparative examples. [Figure 11] FIG. 2 is a cross-sectional view showing a fire resistance test furnace used in the evaluation of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the piping structure of the present invention will be described. As shown in Fig. 1, the piping structure 1 of this embodiment is used as a drainage channel, and includes a pipe joint 10 and a piping material 20. The piping structure 1 of this embodiment is installed by passing through a compartment penetration 2a formed in a floor slab 2 that divides adjacent upper and lower floors. Mortar 3 is filled between the piping structure 1 and the inner surface of the compartment penetration 2a, filling the gap between the inner surface of the compartment penetration 2a and the pipe joint 10 and fixing the piping structure 1 in place.

[0013] (Pipe fittings) The pipe joint 10 in this embodiment comprises a main pipe portion 11 and a side branch pipe connecting portion 12 provided on the main pipe portion 11 . At both ends of the main pipe section 11, there are provided sockets 11a and 11b for connecting the piping material 20 (a first riser pipe 21 and a second riser pipe 22 described later), and at the end of the horizontal branch pipe connection section 12, there is provided a socket 12a for connecting the piping material 20 (a horizontal branch pipe 23 described later). The inner peripheral surface of the socket 11a has an inner diameter that fits closely with the outer peripheral surface of the piping material 20 (the first riser pipe 21), the inner peripheral surface of the socket 11b has an inner diameter that fits closely with the outer peripheral surface of the piping material 20 (the second riser pipe 22), and the inner peripheral surface of the socket 12a has an inner diameter that fits closely with the outer peripheral surface of the piping material 20 (the horizontal branch pipe 23). In this embodiment, the main pipe 11 is a straight pipe. The side branch pipe connection part 12 is curved near the main pipe 11 toward the receiving port 11a in order to smooth the flow of wastewater through the side branch pipe connection part 12. A packing may be attached to the inner peripheral surface of each of the sockets 11a, 11b, 12a so as to fit closely to the outer peripheral surfaces of the pipes 21, 22, 23 to make them watertight.

[0014] The pipe fitting 10 contains a resin composition (A) that includes a thermoplastic resin and a flame retardant. That is, the pipe fitting 10 is produced by molding the resin composition (A). Usually, the pipe fitting 10 is produced by injection molding the resin composition (A). The pipe fitting 10 may have a single-layer structure in which the entire pipe fitting 10 is made of the resin composition (A), or may have a multi-layer structure made of multiple layers. In the case of a multi-layer structure, any one of the layers may be formed from the resin composition (A). For example, when the pipe fitting 10 has a three-layer structure consisting of a surface layer, an intermediate layer, and an inner layer, the intermediate layer may be formed from the resin composition (A). It is preferable that the resin composition (A) constituting the pipe joint 10 does not contain thermally expandable graphite.

[0015] [Resin composition (A)] Examples of the thermoplastic resin contained in the resin composition (A) include crystalline resins and amorphous resins. Examples of the crystalline resins include polyethylene, polypropylene, polybutene, and the like. Examples of the amorphous resins include acrylonitrile-butadiene-styrene copolymer resin (ABS resin), polyvinyl chloride resin, and the like. Since bonding with an adhesive is possible, the amorphous resin is preferred as the thermoplastic resin. In addition, from the viewpoint of flame retardancy, the polyvinyl chloride resin is more preferred as the thermoplastic resin. Examples of polyvinyl chloride resins include polyvinyl chloride homopolymers, copolymers of vinyl chloride monomers and other monomers having unsaturated bonds copolymerizable with vinyl chloride monomers, graft copolymers in which vinyl chloride monomers are graft-copolymerized onto polymers other than polyvinyl chloride resins, etc. The polyvinyl chloride resins may be used alone or in combination of two or more. The polyvinyl chloride resin may be further chlorinated. Examples of the method for chlorinating the polyvinyl chloride resin include a thermal chlorination method and a photochlorination method.

[0016] Examples of other monomers having an unsaturated bond copolymerizable with the vinyl chloride monomer include α-olefins such as ethylene, propylene, and butylene; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as butyl vinyl ether and cetyl vinyl ether; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl acrylate; aromatic vinyls such as styrene and α-methylstyrene; and N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide. The other monomers may be used alone or in combination of two or more.

[0017] Examples of the polymer to be graft-copolymerized with the vinyl chloride monomer include ethylene-vinyl acetate copolymer, ethylene-vinyl acetate-carbon monoxide copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate-carbon monoxide copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, acrylonitrile-butadiene copolymer, polyurethane, chlorinated polyethylene, chlorinated polypropylene, etc. These polymers may be used alone or in combination of two or more.

[0018] The polyvinyl chloride resin may be crosslinked. Examples of a method for crosslinking a polyvinyl chloride resin include a method of adding a crosslinking agent and a peroxide, a method of irradiating with an electron beam, and a method of using a water-crosslinkable material.

[0019] The average degree of polymerization of the polyvinyl chloride resin is preferably from 400 to 1600, and more preferably from 600 to 1400. Here, the average degree of polymerization is an average degree of polymerization measured in accordance with JIS K-6721:1999 "Testing methods for vinyl chloride resins" using a resin sample obtained by dissolving the polyvinyl chloride resin in tetrahydrofuran (THF), removing insoluble components by filtration, and then drying and removing the THF in the filtrate. When the average degree of polymerization of the polyvinyl chloride resin is equal to or higher than the lower limit, the mechanical strength can be sufficiently increased, and when it is equal to or lower than the upper limit, sufficient moldability can be ensured.

[0020] The flame retardant contained in the resin composition (A) is a compound that has an endothermic effect when heated and suppresses temperature rise, or a compound that melts when heated and suppresses the supply of oxygen and the generation of combustible gas. For example, a compound that undergoes an endothermic reaction such as a dehydration reaction when heated can be used as the flame retardant. Examples of heat-absorbing agents include inorganic hydroxides such as magnesium hydroxide, aluminum hydroxide, kaolin minerals (kaolinite, halloysite, dickite) and hydrotalsalcite, and inorganic compounds with water absorption properties such as sepiolite, bentonite, montmorillonite, talc, mica, quartz, zeolite, wollastonite, and nepheline syenite. Hereinafter, inorganic hydroxides and inorganic compounds that undergo a dehydration reaction when heated are collectively referred to as "thermal dehydration type compounds". In thermal dehydration type compounds, the temperature rise can also be suppressed by the latent heat of vaporization of water generated by the dehydration reaction. Among the thermally dehydrated compounds, magnesium hydroxide undergoes a dehydration reaction at temperatures of 300°C or higher. Therefore, when magnesium hydroxide is used as a flame retardant, the occurrence of a dehydration reaction can be suppressed when the resin composition (A) is molded to produce the pipe fitting 10. Among the thermally dehydrated compounds, aluminum hydroxide undergoes a dehydration reaction at about 200°C, and therefore when aluminum hydroxide is used as a flame retardant, it can quickly absorb the heat transferred to the pipe fitting 10 in the event of a fire. Therefore, it is possible to further prevent the pipe fitting 10 from deforming and losing its fire resistance before the piping material 20 (first standpipe 21) thermally expands.

[0021] Among the heat-dehydrated compounds, hydrotalcite has the chemical name magnesium aluminum hydroxide carbonate hydrate, Mg6Al2(OH) 16 It is a type of mineral represented by CO3·4H2O, etc., and consists of a positively charged base layer [Mg 1-x Al x (OH)2] x+ and the negatively charged intermediate layer [(CO3) x / 2 mH2O] x- It is a layered inorganic compound consisting of many divalent and trivalent metals, which have a similar layered structure and can be expressed by the following general formula: [M 2+ 1-x M 3+ x (OH)2] x+ [A n- x / n mH2O]x- M 2+ :Mg 2+ , Zn 2+ Divalent metal ions such as M 3+ :Al 3+ , Fe 3+ Trivalent metal ions such as A n- :CO3 2- , Cl - , NO3 - n-valent anions such as X:0 <X≦0.33 In hydrotalcite, the water of crystallization between molecules starts to dehydrate at about 180°C, and the water of crystallization is completely eliminated at about 300°C. Up to this state, synthetic hydrotalcite maintains its crystal structure, but when the temperature exceeds about 350°C, the crystal structure starts to collapse, releasing water and carbon dioxide. Synthetic hydrotalcite starts its endothermic decomposition at a temperature that is 60°C to 75°C lower than the thermal decomposition temperature of polyvinyl chloride resin, which is about 200°C to 300°C, and therefore the thermal decomposition of polyvinyl chloride resin can be efficiently suppressed by the endothermic decomposition of hydrotalcite. The flame retardant may be a combination of at least two of magnesium hydroxide, aluminum hydroxide, kaolin-based minerals, and hydrotalcite.

[0022] The heat-dehydrating compound is usually in the form of particles. The volume average particle diameter of the thermally dehydrated compound is preferably 0.01 μm or more and 20 μm or less, more preferably 0.05 μm or more and 2 μm or less, and even more preferably 0.05 μm or more and 1 μm or less. By setting the volume average particle diameter of the thermally dehydrated compound within this range, it is possible to impart transparency to the pipe joint 10 and improve the dispersibility of the thermally dehydrated compound. The volume average particle diameter is a value measured using a laser diffraction scattering method particle size distribution measuring device. The BET specific surface area of ​​the thermally dehydrated compound is 1m 2 / g or more 40m 2 / g or less, and 1m 2 / g or more 20m 2 / g or less. Here, the BET specific surface area is a value determined by utilizing nitrogen adsorption. When the volume average particle diameter and BET specific surface area of ​​the thermally dehydrated compound are within the above ranges, the compound can fully exert its effect as a flame retardant, and the moldability of the resin composition (A) when producing the pipe fitting 10 and the mechanical properties of the pipe fitting 10 can be fully ensured.

[0023] The particle surface of the thermally dehydrated compound is preferably treated with a surface treatment agent such as a higher fatty acid such as stearic acid or a silane coupling agent. The thermally dehydrated compound that has been surface-treated with a surface treatment agent has high dispersibility in thermoplastic resins and is more likely to exhibit the endothermic effect. In addition, when the thermally dehydrated compound is basic, it can make the thermoplastic resin less susceptible to scorching and prevent yellowing. When the thermally dehydrated compound is surface-treated with a surface treatment agent, the amount of the surface treatment agent is preferably 0.05 parts by mass or more and 2.0 parts by mass or less relative to 100 parts by mass of the thermally dehydrated compound. When the amount of the surface treatment agent is equal to or more than the lower limit, the dispersibility of the thermally dehydrated compound in the thermoplastic resin can be sufficiently increased, and when the amount is equal to or less than the upper limit, a decrease in economic efficiency can be suppressed.

[0024] Examples of flame retardants other than the heat absorbing agent include hydrotalcite, antimony oxide, molybdenum compounds, bromine-based compounds, phosphorus-based compounds, and boric acid-based compounds. Examples of antimony oxide include antimony dioxide, antimony trioxide, and antimony pentoxide. Examples of the molybdenum compound include molybdenum trioxide, molybdenum disulfide, and ammonium molybdate. Examples of the brominated compounds include tetrabromobisphenol A, tetrabromoethane, tetrabromoethane, and tetrabromoethane. Examples of phosphorus compounds include red phosphorus, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, xylenyl diphenyl phosphate, sodium phosphate, potassium phosphate, magnesium phosphate, zinc phosphate, and ammonium polyphosphate. Examples of the boric acid compound include calcium borate and zinc borate. Among the flame retardants, phosphorus compounds and antimony trioxide are preferred because they have a high effect of inhibiting the combustion of polyvinyl chloride resin. These flame retardants may be used alone or in combination of two or more.

[0025] The content of the flame retardant in the resin composition (A) is preferably 0.01 to 10.0 parts by mass, more preferably 0.05 to 5.0 parts by mass, and even more preferably 0.1 to 2.0 parts by mass, relative to 100 parts by mass of the thermoplastic resin. If the content of the flame retardant in the resin composition (A) is equal to or greater than the lower limit, deformation of the pipe fitting 10 in the event of a fire can be further suppressed. If the content of the flame retardant is equal to or less than the upper limit, moldability during production of the pipe fitting 10 can be sufficiently increased, and the mechanical properties of the pipe fitting 10 can be improved.

[0026] In addition, the resin composition (A) may contain additives such as lubricants, processing aids, impact modifiers, heat resistance improvers, antioxidants, heat stabilizers, heat stabilization aids, light stabilizers, ultraviolet absorbers, pigments, plasticizers, and thermoplastic elastomers, as long as the effects of the present invention are not impaired. The additives described below may be used alone or in combination of two or more kinds.

[0027] The lubricant includes an internal lubricant and an external lubricant. Examples of internal lubricants include butyl stearate, lauryl alcohol, stearyl alcohol, epoxidized soybean oil, glycerin monostearate, stearic acid, bisamides, and the like. Examples of the external lubricant include paraffin wax, polyolefin wax, ester wax, and montanic acid wax.

[0028] Examples of the processing aid include alkyl acrylate-alkyl methacrylate copolymers having a mass average molecular weight of 100,000 to 2,000,000. Examples of the alkyl acrylate-alkyl methacrylate copolymers include n-butyl acrylate-methyl methacrylate copolymers, 2-ethylhexyl acrylate-methyl methacrylate-butyl methacrylate copolymers, etc.

[0029] Examples of impact modifiers include methyl methacrylate-butadiene-styrene copolymer (MBS), chlorinated polyethylene, acrylic rubber, and the like. Examples of the heat resistance improver include α-methylstyrene resins and N-phenylmaleimide resins.

[0030] Examples of the antioxidant include phenol-based antioxidants and phosphorus-based antioxidants.

[0031] Examples of the heat stabilizer include a lead-based stabilizer, a tin-based stabilizer, a Ca-Zn-based stabilizer, a higher fatty acid metal salt, etc. The heat stabilizer may be used alone or in combination of two or more kinds. Examples of lead-based stabilizers include white lead, basic lead sulfite, tribasic lead sulfate, dibasic lead phosphite, dibasic lead phthalate, tribasic lead maleate, silica gel coprecipitated lead silicate, dibasic lead stearate, lead stearate, and lead naphthenate. Examples of tin-based stabilizers include mercaptides such as dibutyltin mercapto, dioctyltin mercapto, and dimethyltin mercapto; malates such as dibutyltin maleate, dibutyltin maleate polymer, dioctyltin maleate, and dioctyltin maleate polymer; and carboxylates such as dibutyltin mercaptodibutyltin laurate and dibutyltin laurate polymer. The Ca-Zn stabilizer is a mixture of a fatty acid salt of calcium and a fatty acid salt of zinc. The fatty acid includes behenic acid, stearic acid, lauric acid, oleic acid, palmitic acid, ricinoleic acid, benzoic acid, etc., and two or more of these may be used in combination. Examples of higher fatty acid metal salts include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, cadmium stearate, cadmium laurate, cadmium ricinoleate, cadmium naphthenate, cadmium 2-ethylhexanoate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexanoate, lead stearate, dibasic lead stearate, and lead naphthenate. Among these, when making the pipe fitting 10 transparent, tin-based stabilizers or Ca-Zn-based stabilizers are preferred, and as tin-based stabilizers, those that do not contain sulfur, such as malates and carboxylates, are particularly preferred in order to prevent sulfide contamination, and as Ca-Zn-based stabilizers, stearates are particularly preferred in view of the balance between lubricity and plate-out during molding processing.

[0032] The content of the heat stabilizer is preferably 0.3 parts by mass or more and 5.0 parts by mass or less relative to 100 parts by mass of the thermoplastic resin. If the content of the heat stabilizer is equal to or more than the lower limit, the thermal stability of the thermoplastic resin during molding can be improved, and if the content is equal to or less than the upper limit, the thermoplastic resin can be sufficiently carbonized during combustion, and sufficient fire resistance can be obtained.

[0033] Examples of the heat stabilization aid include epoxidized soybean oil, phosphoric acid esters, polyols, hydrotalcite, and zeolites. Examples of the light stabilizer include hindered amine light stabilizers. Examples of the ultraviolet absorbing agent include salicylic acid ester-based ultraviolet absorbing agents, benzophenone-based ultraviolet absorbing agents, benzotriazole-based ultraviolet absorbing agents, and cyanoacrylate-based ultraviolet absorbing agents.

[0034] Examples of pigments include organic pigments such as azo pigments, phthalocyanine pigments, threne pigments, and dye lakes; and inorganic pigments such as oxide pigments, molybdenum chromate pigments, sulfide / selenide pigments, and ferrocyanide pigments.

[0035] Examples of the plasticizer include dibutyl phthalate, di-2-ethylhexyl phthalate, di-2-ethylhexyl adipate, etc. However, since the plasticizer tends to reduce the heat resistance and fire resistance of the molded product, it is preferable to use a small amount of the plasticizer.

[0036] Examples of thermoplastic elastomers include acrylonitrile-butadiene copolymers (NBR), ethylene-vinyl acetate copolymers (EVA), ethylene-vinyl acetate-carbon monoxide copolymers (EVACO), vinyl chloride-based thermoplastic elastomers such as vinyl chloride-vinyl acetate copolymers and vinyl chloride-vinylidene chloride copolymers, styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, urethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, and polyamide-based thermoplastic elastomers.

[0037] [Manufacturing method of pipe joints] The pipe joint 10 can be manufactured by any of the conventional methods known in the art, such as extrusion molding, injection molding, and blow molding.

[0038] (Piping materials) The piping materials 20 in this embodiment include a first standpipe 21, a second standpipe 22, and a lateral branch pipe 23. The first riser pipe 21 is disposed vertically downward relative to the floor slab 2, and its upper end is connected to the lower socket 11a of the pipe joint 10. The upper end of the first riser pipe 21 is inserted into the compartment penetration portion 2a. The second riser pipe 22 is disposed vertically upward relative to the floor slab 2, and its lower end is connected to the upper socket 11b of the pipe joint 10. One end of the horizontal branch pipe 23 is connected to the socket 12a of the horizontal branch pipe connection part 12, and is disposed at an incline so that the height gradually increases as the pipe moves away from the socket 12a. However, since the installation space for the horizontal branch pipe 23 is limited, the inclination of the horizontal branch pipe 23 is set to a slight angle, for example, an angle of 10° or less with respect to the horizontal direction.

[0039] The piping material 20 contains a resin composition (B) containing a thermoplastic resin and thermally expandable graphite. That is, the piping material 20 is produced by molding the resin composition (B) and contains a thermoplastic resin and thermally expandable graphite. Usually, the piping material 20 is produced by extrusion molding the resin composition (B). The piping material 20 may have a single-layer structure in which the entire piping material 20 is made of the resin composition (B), or may have a multi-layer structure made of multiple layers. That is, the piping material 20 has a tubular peripheral wall of a single-layer structure or a multi-layer structure. When the piping material 20 has a multi-layer structure, any one of the layers may be formed from the resin composition (B). For example, when the piping material 20 has a three-layer structure consisting of a surface layer, an intermediate layer, and an inner layer, the intermediate layer may be formed from the resin composition (B), and the surface layer, the intermediate layer, and the inner layer may contain a flame retardant. The surface layer is located on the outer peripheral surface of the tubular intermediate layer, and the inner layer is located on the inner peripheral surface of the intermediate layer. The intermediate layer is black in color because it contains thermally expandable graphite, so it is preferable that the surface layer and the inner layer contain a colorant other than black so that they can be distinguished from the intermediate layer. In this embodiment, the intermediate layer is a fire-resistant layer. Also, in this embodiment, the surface layer and the inner layer are coating layers, and the inner layer is an inner coating layer.

[0040] The size of the piping material 20 is, for example, a nominal diameter of 40 (outer diameter 48 mm) or more and a nominal diameter of 300 (outer diameter 318 mm) or less. Since the present invention has high compressive strength, it is particularly effective for piping materials of medium diameter (nominal diameter 65 (outer diameter 76 mm) or more and nominal diameter 125 (outer diameter 140 mm) or less) that are prone to breakage, and is particularly effective for piping materials of large diameter (nominal diameter 150 (outer diameter 165 mm) or more and nominal diameter 300 (outer diameter 318 mm) or less). The SDR (outer diameter / thickness (wall thickness) of the piping material) is, for example, preferably 13 to 35, more preferably 15 to 33, and even more preferably 17 to 30. If the SDR is equal to or greater than the lower limit, the thermally expandable graphite is more likely to be oriented in the circumferential direction of the piping material 20, which increases the compressive strength and reduces the thermal conductivity. If the SDR is equal to or less than the upper limit, the wall thickness does not become too thin, which increases the compressive strength and increases the fire resistance.

[0041] In the case of a multi-layer structure, the intermediate layer may be a foamed layer or a non-foamed layer. By using a foamed layer as the intermediate layer, the thermal conductivity can be further reduced. For example, in the case of a nominal diameter of 100A (outer diameter of 114mm), the thickness of the intermediate layer is preferably 1.8mm to 7.6mm, more preferably 2.0mm to 6.0mm, and even more preferably 2.5mm to 5.0mm. The thickness of the intermediate layer is preferably 85% or less of the thickness of the piping material, more preferably 70% or less, and even more preferably 60% or less. If the thickness of the intermediate layer is within the above range, the fire resistance and compressive strength can be further increased.

[0042] In the case of a multi-layer structure, the surface layer and the inner layer may be foamed layers or non-foamed layers. By making the surface layer and the inner layer non-foamed layers, the strength of the piping material can be further increased. For example, in the case of a nominal diameter of 100A (outer diameter of 114mm), the thickness of the surface layer and the inner layer is preferably 0.3 mm to 3.0 mm, and more preferably 0.6 mm to 1.5 mm. If the thickness of the coating layer is 0.3 mm or more, the mechanical strength of the pipe can be sufficiently ensured, and if it is 3.0 mm or less, the decrease in fire resistance can be suppressed.

[0043] The compression ratio of the piping material 20 is preferably 20% or more, more preferably 30% or more, even more preferably 40% or more, and particularly preferably 50% or more. If the compression ratio is equal to or more than the lower limit, the piping material is less likely to break even if it is subjected to a crushing force during transportation or piping. In addition, the thermally expandable graphite is oriented in the circumferential direction of the piping material 20, which reduces the thermal conductivity. The upper limit of the compression ratio of the piping material 20 is substantially 90% or less. The compression ratio of the piping material 20 is measured by the flattening test of JIS K 6741:2007. A ring-shaped test piece of 50 mm or more is cut from the piping material and left at 23°C for one hour, and then sandwiched between two flat plates and compressed at a speed of 10 mm / min in a direction perpendicular to the pipe axis. The degree of radial compression at the time of destruction of three ring-shaped test pieces is measured, and the average value is taken as the compression ratio. For example, if the piping material is destroyed when the outer diameter becomes 2 / 3, the compression ratio is 33%, since the compression ratio is 1 / 3 of the outer diameter, i.e., 33% of the outer diameter, is compressed. The compression ratio of the piping material 20 can be adjusted by combining compositional aspects such as the amount and aspect ratio of thermally expandable graphite and the type of flame retardant, with structural aspects such as the SDR of the piping material, the position of the weld line, the layer structure of the piping material, and the thickness of each layer.

[0044] The thermal conductivity of the piping material 20 is preferably equal to or less than 0.3 W / m·K, more preferably equal to or less than 0.28 W / m·K, and even more preferably equal to or less than 0.25 W / m·K. If the thermal conductivity is equal to or less than the above upper limit, the piping material 20 is less likely to cause condensation. The thermal conductivity of the piping material 20 is a value measured in the thickness direction of the piping material 20 at three locations under the condition of 23° C. in accordance with JIS A1412-2:1999. The thermal resistance value of the piping material 20 (value obtained by dividing the thickness by the thermal conductivity) is 0.03 mm. 2 K / W or more is preferable, 0.04m 2 K / W or higher is more preferable.

[0045] [Resin composition (B)] As the thermoplastic resin contained in the resin composition (B), the same thermoplastic resin as that contained in the resin composition (A) can be used, and from the viewpoint of flame retardancy, a polyvinyl chloride resin is preferred. Furthermore, various additives may be contained in the resin composition (B). The additives may be the same as those that may be contained in the resin composition (A).

[0046] The thermal expansion start temperature of the thermally expandable graphite contained in the resin composition (B) is preferably 200°C or more and 285°C or less, more preferably 210°C or more and 285°C or less, and even more preferably 240°C or more and 285°C or less. As described below, in the manufacturing method of the piping material 20, the resin composition is extruded with a die and molded into a tubular shape. At this time, the resin composition flows so as to wrap around in the circumferential direction in the die. Therefore, at the position where the resin composition wraps around and the resin compositions butt against each other, a weld line extending in the axial direction of the pipe material 20 is formed. If the thermal expansion start temperature is equal to or higher than the above lower limit, the temperature when extruding with the die during the manufacturing of the piping material 20 can be increased, so that the weld line adheres to each other and the compressive strength can be further increased. In addition, if the thermal expansion start temperature is equal to or higher than the above lower limit, gas generation due to the expansion of the thermally expandable graphite is suppressed during the manufacturing of the piping material 20, and the weld line adheres to each other well, so that the compressive strength can be further increased. The thermal expansion starting temperature of thermally expandable graphite is the temperature at which the thermally expandable graphite expands to at least 1.1 times its volume before the start of heating when the temperature is increased from 150° C. at a heating rate of 5° C. / min. The temperature interval at which the volume of the thermally expandable graphite is measured is not particularly limited, and the volume may be measured every time the temperature increases by 5° C., for example. The thermal expansion starting temperature equal to or higher than the lower limit is sufficiently higher than the molding temperature when the resin composition (B) is molded to produce the piping material 20. Therefore, when the thermal expansion starting temperature of the thermally expandable graphite is equal to or higher than the lower limit, the thermally expandable graphite can be prevented from expanding when the resin composition (B) is molded.

[0047] The thermally expandable graphite is flaky graphite and has a flat plate shape. The flaky shape of the thermally expandable graphite allows it to expand sufficiently by heating. The flaky shape means a thin piece or a flat plate shape, and for example, the aspect ratio described later is 5 or more.

[0048] In addition, thermally expandable graphite has a degree of expansion of 180 cm at 1000°C. 3 / g or more, and 3 / g or more. Here, the degree of expansion of the thermally expandable graphite at 1000°C is the volume (cm) per unit mass (g) after the thermally expandable graphite is held at 1000°C for 10 seconds. 3 ) If the degree of expansion of the thermally expandable graphite is equal to or greater than the lower limit, it will expand sufficiently, so that the compartment penetration portion 2a can be more reliably closed in the event of a fire. The degree of expansion of thermally expandable graphite at 1000°C is set to 240cm because this makes it easier to manufacture thermally expandable graphite. 3 It is preferable that the molecular weight is not more than 1 / g.

[0049] The above-mentioned thermally expandable graphite can be obtained by treating graphite powder with an inorganic acid and an oxidizing agent. This treatment can produce a crystalline compound in which the inorganic acid is inserted between the graphite layers. The crystalline compound in which the inorganic acid is inserted between the graphite layers has thermal expandability. Examples of the graphite include natural flaky graphite, pyrolytic graphite, and kish graphite. Examples of the inorganic acid include concentrated sulfuric acid, nitric acid, and selenic acid. Examples of the oxidizing agent include concentrated nitric acid, perchloric acid, perchlorates, permanganates, dichromates, and hydrogen peroxide. After the graphite powder has been treated with the inorganic acid and the oxidizing agent, it may be subjected to a neutralization treatment to reduce the acidity.

[0050] The pH of the thermally expandable graphite is preferably 2 or more and 10 or less, more preferably 2.5 or more and 8 or less. When the resin composition (B) contains a heat-absorbing agent having hydroxide ions such as magnesium hydroxide or aluminum hydroxide as a flame retardant, the hydroxide ions of the flame retardant neutralize with the acidic substance to generate water (neutralized water). The hydroxide ions used in the condensation reaction of hydroxide ions, which is an endothermic reaction, are reduced by the neutralization reaction during molding, so that the amount of heat absorbed during a fire is reduced. In addition, bubbles may be generated by the evaporation of the neutralized water. Therefore, by setting the pH of the thermally expandable graphite to the above lower limit value or more, neutralization with the flame retardant can be suppressed. If the pH of the thermally expandable graphite is the above upper limit value or less, the thermally expandable graphite is less likely to be neutralized and expands better. The method for adjusting the pH of the thermally expandable graphite is not particularly limited. For example, when producing the thermally expandable graphite, a method may be used in which graphite powder is treated with an inorganic acid and an oxidizing agent, and then the treatment is repeated with water washing and drying to adjust the pH of the thermally expandable graphite. The pH of the thermally expandable graphite is a value measured by the following method. Put 5 g of the collected thermally expandable graphite and 25 ml of ion-exchanged water into a beaker to prepare a graphite mixture. Stir the prepared graphite mixture for 30 seconds, leave it for 20 minutes, and then measure the pH of the graphite mixture using a pH meter (HORIBA, Ltd. "pH / ION METER F-23").

[0051] The average particle size of the thermally expandable graphite is preferably 10 μm or more and 1000 μm or less, more preferably 100 μm or more and 700 μm or less, and the average thickness is preferably 100 μm or less. The average particle size of the thermally expandable graphite is the 50% particle size in the cumulative particle size distribution on a volume basis, which is determined by sieving the thermally expandable graphite with a test sieve of JIS Z8801-1.

[0052] The average aspect ratio of the thermally expandable graphite is 5 to 40, preferably 10 to 35, and more preferably 20 to 35. That is, the thermally expandable graphite is a flat flake. If the aspect ratio is equal to or greater than the lower limit, the degree of expansion is likely to be low. If the aspect ratio is equal to or less than the upper limit, the thermal conductivity can be further reduced. In addition, if the aspect ratio is equal to or less than the upper limit, the difference in linear expansion coefficient between the layer containing thermally expandable graphite and the layer not containing it can be reduced when the piping material has a multi-layer structure, and molding defects such as peeling of the intermediate layer and the surface layer due to the influence of shrinkage difference caused by cleaning of the inside of the piping material or heat from high-temperature wastewater, or warping of the piping material due to a large difference in shrinkage between the surface layer and the intermediate layer after molding can be suppressed. The thermally expandable graphite, which is a flat flake, is oriented along the circumferential direction of the piping material 20. At the position of the weld line, the thermally expandable graphite is likely to be oriented in the radial direction of the piping material 20. Therefore, at the position of the weld line, flat surfaces of the thermally expandable graphite face each other, making it easy for cracks to occur. If the aspect ratio is equal to or less than the above upper limit, the area of ​​the thermally expandable graphite facing each other at the position of the weld line becomes small, and the compressive strength can be increased.

[0053] The linear expansion coefficient of the rigid polyvinyl chloride resin constituting the piping material 20 is 7.0×10 as measured by the thermomechanical analysis method (TMA method) specified in JIS K 7197:2012. -5 / ℃, the piping material of this embodiment is 4.5×10 -5 / ℃ or more 7.0×10 -5 / ℃ is less than 5.0×10 -5 / ℃ or more 7.0×10 -5 / ℃, preferably less than 5.5×10 -5 / ℃ or more 6.8×10 -5 / °C. The difference in linear expansion coefficient between the surface layer, inner layer, and intermediate layer is preferably less than 2.5×10 -5 / ℃ or less, 2.0×10 -5 / ℃ or less is preferable, and 1.0×10 -5 / °C or less is more preferable.

[0054] Furthermore, the fusion strength between the surface layer, inner layer and intermediate layer of the piping material is preferably 1.5 MPa or more, more preferably 2.0 MPa or more. The higher the fusion strength, the easier it is to increase the compressive strength of the piping material. The fusion strength between the surface layer, inner layer and intermediate layer can be adjusted by a combination of the aspect ratio of the thermally expandable graphite, the amount of thermally expandable graphite, and the degree of vacuum in a sizing device in the manufacturing method described later.

[0055] The average aspect ratio is the ratio of the length of the longest part in a plan view to the thickness. Since the thermally expandable graphite used in the present invention is generally flat, if the thickness direction is considered to be the vertical direction and the radial direction is considered to be the horizontal direction, the aspect ratio is the value obtained by dividing the maximum dimension in the horizontal direction by the thickness in the vertical direction.

[0056] Then, the aspect ratio is measured for a sufficiently large number of graphite pieces, i.e., at least 10 or more, and the average value is taken as the average aspect ratio. More specifically, the thermally expandable graphite is observed using an FE-SEM, the image is read into image processing software ("Photoshop (registered trademark)" manufactured by Adobe Systems Incorporated), and the maximum dimension and thickness are measured using a length measurement tool. Regarding the maximum dimension, when measuring the graphite particles before being added to the resin composition, the maximum side of a rectangle circumscribing the graphite particles is taken as the maximum dimension. When measuring the maximum dimension of the graphite particles after being added to the resin composition, the piping material 20 is cut and the cross section is observed to take the long side as the maximum dimension, or the graphite particles are extracted from the piping material 20, and the maximum side of a rectangle circumscribing the extracted graphite particles is taken as the maximum dimension. Note that the specific dimensions can be measured by measuring the scale bar in the FE-SEM image in the same manner.

[0057] The maximum horizontal dimension of the thermally expandable graphite and the thickness of the exfoliated graphite can be measured using, for example, a field emission scanning electron microscope (FE-SEM).

[0058] The content of the thermally expandable graphite in the resin composition (B) is preferably 3.0 parts by mass or more and 20.0 parts by mass or less, more preferably 4.0 parts by mass or more and 18.0 parts by mass or less, even more preferably 4.0 parts by mass or more and 15.0 parts by mass or less, and particularly preferably 4.0 parts by mass or more and less than 10.0 parts by mass, relative to 100 parts by mass of the thermoplastic resin. If the content of the thermally expandable graphite in the resin composition (B) is equal to or more than the lower limit, the piping material 20 (particularly the first standpipe 21) can be sufficiently expanded in the event of a fire, and the fire resistance of the compartment penetration part 2a can be further improved. On the other hand, if the content of the thermally expandable graphite in the resin composition (B) is equal to or less than the upper limit, the piping material 20 can be prevented from being broken due to excessive expansion of the piping material 20, and the fire resistance can be prevented from being reduced. In addition, if the content of the thermally expandable graphite in the resin composition (B) is equal to or less than the upper limit, the thermal conductivity of the piping material 20 can be reduced, and the pressure resistance and compressive strength can be further increased.

[0059] In addition to the thermally expandable graphite, the resin composition (B) preferably contains a flame retardant. The flame retardant in the resin composition (B) may be the same as that in the resin composition (A). As the flame retardant in the resin composition (B), heat-dehydrated compounds such as aluminum hydroxide, magnesium hydroxide, and magnesium carbonate, molybdenum compounds, bromine compounds, phosphorus compounds, and boric acid compounds are preferred. When these flame retardants are included, the fire resistance of the piping material 20 can be further improved. The content of the flame retardant in the resin composition (B) is preferably from 0.05 to 10 parts by mass, more preferably from 1 to 5 parts by mass, per 100 parts by mass of the thermoplastic resin. In addition, the content of the flame retardant is preferably 13 parts by mass or more and 215 parts by mass or less, more preferably 13 parts by mass or more and 190 parts by mass or less, even more preferably 17 parts by mass or more and 130 parts by mass or less, and most preferably 40 parts by mass or more and 120 parts by mass or less, relative to 100 parts by mass of the thermally expandable graphite contained in the thermoplastic resin. When the content of the flame retardant is equal to or greater than the lower limit, the fire resistance can be further improved, and when the content is equal to or less than the upper limit, the mechanical strength of the piping material 20 can be sufficiently increased. In particular, when part or all of the flame retardant is a phosphorus-based compound, the mechanical strength is likely to decrease, so the content of the phosphorus-based compound is preferably 1 part by mass or more and less than 200 parts by mass, and more preferably 13 parts by mass or more and 150 parts by mass or less, per 100 parts by mass of thermally expandable graphite contained in the thermoplastic resin.

[0060] The volume average particle size of the flame retardant is preferably from 0.2 μm to 100 μm, more preferably from 0.4 μm to 50 μm. The volume average particle size of the flame retardant is a value measured by a light scattering particle size meter (light scattering particle size meter DLS-7000: manufactured by Otsuka Electronics Co., Ltd.). When the resin composition (B) contains a flame retardant, the ratio of the average particle size α of the thermally expandable graphite to the volume average particle size β of the flame retardant (β / α ratio) is preferably 0.0015 to 0.0065, more preferably 0.002 to 0.006. The flame retardant acts as a thermal bridge between the thermally expandable graphite particles. If the β / α ratio is within the above range, the thermal bridge is prevented, and the thermal conductivity can be further reduced.

[0061] The resin composition (B) may contain a heat stabilizer. Examples of the heat stabilizer include lead-based stabilizers, tin-based stabilizers, Ca-Zn-based stabilizers, higher fatty acid metal salts, etc. The heat stabilizers may be used alone or in combination of two or more.

[0062] Examples of lead-based stabilizers include white lead, basic lead sulfite, tribasic lead sulfate, dibasic lead phosphite, dibasic lead phthalate, tribasic lead maleate, silica gel coprecipitated lead silicate, dibasic lead stearate, lead stearate, and lead naphthenate. Examples of tin-based stabilizers include mercaptides such as dibutyltin mercapto, dioctyltin mercapto, and dimethyltin mercapto; malates such as dibutyltin maleate, dibutyltin maleate polymer, dioctyltin maleate, and dioctyltin maleate polymer; and carboxylates such as dibutyltin mercaptodibutyltin laurate and dibutyltin laurate polymer. The Ca-Zn stabilizer is a mixture of a fatty acid salt of calcium and a fatty acid salt of zinc. The fatty acid includes behenic acid, stearic acid, lauric acid, oleic acid, palmitic acid, ricinoleic acid, benzoic acid, etc., and two or more of these may be used in combination. Examples of higher fatty acid metal salts include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, cadmium stearate, cadmium laurate, cadmium ricinoleate, cadmium naphthenate, cadmium 2-ethylhexanoate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexanoate, lead stearate, dibasic lead stearate, and lead naphthenate.

[0063] The content of the heat stabilizer is preferably 0.3 parts by mass or more and 5.0 parts by mass or less relative to 100 parts by mass of the thermoplastic resin. If the content of the heat stabilizer is equal to or more than the lower limit, the thermal stability of the thermoplastic resin during molding can be improved, and if the content is equal to or less than the lower limit, the thermoplastic resin can be sufficiently carbonized during combustion, and sufficient fire resistance can be obtained.

[0064] The resin composition (B) preferably contains an inorganic filler in addition to the thermally expandable graphite. Examples of the inorganic filler include inorganic compounds other than the flame retardants, such as silica, diatomaceous earth, alumina, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, calcium hydroxide, basic magnesium carbonate, calcium carbonate, zinc carbonate, barium carbonate, dawnnite, hydrotalcite, calcium sulfate, barium sulfate, gypsum fiber, calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass fiber, glass beads, silica-based balloon, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon fiber, carbon balloon, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, stainless steel fiber, zinc phosphate, zinc borate, various magnetic powders, slag fiber, fly ash, and dehydrated sludge. Among the above inorganic fillers, basic inorganic fillers such as calcium carbonate, calcium silicate, calcium hydroxide, calcium oxide, magnesium oxide, barium carbonate, zinc oxide, zinc hydroxide, and iron oxide are preferred. The inorganic fillers may be used alone or in combination of two or more kinds.

[0065] The content of the inorganic filler is preferably 0.3 parts by mass or more and 50.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 5.0 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. If the content of the inorganic filler is equal to or more than the lower limit, the fire resistance can be further improved, and if it is equal to or less than the upper limit, the mechanical strength of the piping material 20 can be made sufficiently high. In particular, when a thermally expandable graphite having a pH adjusted to 1.5 or more and 4.0 or less is used, the resin composition (B) preferably contains the basic inorganic filler in a ratio of 0.3 parts by mass to 5.0 parts by mass relative to 100 parts by mass of the thermoplastic resin. If the content ratio of the basic inorganic filler is equal to or more than the lower limit, the thermal stability of molding the resin composition (B) to produce the piping material 20 is increased, and the generation of char during molding can be prevented, and if the content ratio is equal to or less than the upper limit, the thermoplastic resin can be sufficiently carbonized in the event of a fire, and the fire resistance can be further improved.

[0066] [Manufacturing method of piping materials] A piping material having a three-layer structure consisting of a surface layer, a middle layer, and an inner layer is manufactured, for example, by using a manufacturing apparatus 60 shown in FIG. The manufacturing apparatus 60 in this example includes a first extrusion molding machine 61 , a second extrusion molding machine 62 , a vacuum sizing device 63 , a take-up machine 64 , and a cutter 65 .

[0067] The first extruder 61 includes a first extruder 68 for kneading, heating, melting, and extruding the resin composition supplied from a hopper 66. The second extruder 62 includes a second extruder 69 for kneading, heating, melting, and extruding the resin composition supplied from a hopper 67. A die 70 is attached to the outlet of the first extruder 68 and the second extruder 69. The hopper 66 of the first extruder 61 is supplied with a resin composition (B-2) constituting the surface layer and the inner layer of the piping material. The hopper 67 of the second extruder 62 is supplied with a resin composition (B-1) constituting the intermediate layer. It is preferable that at least the resin composition (B-1) contains a thermoplastic resin and thermally expandable graphite.

[0068] 3, the mold 70 is a three-layer extrusion mold, and includes a confluence section 71 and a molding section 72. In the confluence section 71, a molten resin (molten resin composition (B-2)) 73 introduced from a first extruder 68 and a molten resin (molten resin composition (B-1)) 74 introduced from a second extruder 69 join together, and these are laminated near the outlet of the confluence section 71. The behavior of the molten resins 73, 74 in the mold 70 will be described. 4(a) to 4(g) are end views taken at the positions (a) to 4(g) of FIG. 3, respectively. As shown in Fig. 3, molten resin 73 branches into molten resins 73a and 73b inside mold 70. As shown in Figs. 4(a) to (e), molten resin 74 forming the intermediate layer gradually changes shape from U-shape (Fig. 4(a)), to C-shape (Figs. 4(b) to (d)), to O-shape (Fig. 4(e)) so as to surround molten resin 73a forming the inner layer, and is molded into an annular cross section. As shown in Fig. 4(e), a weld line of the intermediate layer is formed in molten resin 74 at position L1 where the ends of molten resin 74 are butted together. The weld line of the intermediate layer extends in the axial direction of piping material 20. As shown in Figs. 4(c) to (f), the molten resin 73a gradually changes from a circular shape (Fig. 4(c)), to a U-shape (Fig. 4(e)), to a C-shape (Fig. 4(f)), to an O-shape (Fig. 4(g)) inside the annular molten resin 74, and is molded into an annular cross section. The molten resin 73b gradually changes from a U-shape (Fig. 4(e)), to a C-shape (Fig. 4(f)), to an O-shape (Fig. 4(g)) outside the annular molten resin 74, and is molded into an annular cross section surrounding the molten resin 74. As shown in Fig. 4(g), a weld line of the inner layer is formed at a position L2 where the ends of the molten resin 73a are butted together. As shown in Fig. 4(g), a weld line of the surface layer is formed at a position L3 where the ends of the molten resin 73b are butted together. The weld lines of the inner layer and the surface layer extend in the axial direction of the piping material 20. In this embodiment, the weld line of the intermediate layer and the weld lines of the inner layer and the surface layer are formed on the opposite side of the tube axis O1. In this way, the weld line of the intermediate layer and the weld lines of the inner layer and the surface layer are formed at different positions, thereby further increasing the compressive strength of the piping material. In the cross section (cross section perpendicular to the tube axis) of the piping material 20, it is preferable that the weld line of the intermediate layer and the weld line of the inner layer or the surface layer are not located in an area rotated 45° around the tube axis as the rotation center. That is, it is preferable that the positions L2 and L3 are not located in the areas q1 and q2 in FIG. 4(g). In FIG. 4(g), the area q1 is an area up to a straight line Q1 rotated 45° counterclockwise around the tube axis O1 as the rotation axis with respect to the line Q connecting the position L1 of the weld line of the intermediate layer and the tube axis O1. In FIG. 4(g), region q2 is a region extending to a straight line Q2 that is rotated 45° clockwise with the tube axis O1 as the axis of rotation with respect to a line Q connecting the position L1 of the weld line of the intermediate layer and the tube axis O1.

[0069] 4(g), the laminated molten resins 73, 74 are expanded in diameter while remaining laminated in the molding section 72 to become tubular. Then, the outer and inner circumferences are restricted to a more or less appropriate size by a die ring 75 and a mandrel 76 provided at the tip of the molding section 72, and the resin is extruded as a continuous piping material (hereinafter referred to as a "continuous pipe") 77.

[0070] At this time, the molding temperature of the mold 70 (resin temperature during molding) is preferably adjusted to 175° C. or higher and lower than 240° C. The molding temperature is more preferably 180° C. or higher and 235° C. or lower, even more preferably 185° C. or higher and 230° C. or lower, and particularly preferably 190° C. or higher and 225° C. or lower. By setting the molding temperature within the above range, it is possible to improve the adhesion between the intermediate layer containing thermally expandable graphite in a well-kneaded state and the surface layer and inner layer. If the molding temperature is less than 170°C, the resin composition (B-1) containing the thermally expandable graphite will be poorly kneaded, and the flowability in the mold 70 will decrease, making molding difficult. If the molding temperature is more than 240°C, the thermally expandable graphite contained in the resin composition (B-1) will expand in the mold 70.

[0071] In addition, it is preferable that the molding temperature is adjusted so that it gradually becomes higher from the first extruder 61 and the second extruder 62 to the mold 70. Specifically, the resin temperature at the connection portion between the first extruder 68 and the second extruder 69 and the mold 70 is set higher than the resin temperature of a general piping material, and is preferably 150°C or higher and the mold temperature or lower, and more preferably 170°C or higher and the mold temperature or lower. The resin temperatures in the first extruder 68 and the second extruder 69 may be the same or different from each other. By making the resin temperature in the second extruder 62, which kneads the resin composition (B-1) containing thermally expandable graphite, higher than the resin temperature in the first extruder 61, the fluidity of the resin is increased, making it easier to knead, and making it easier to supply the resin to the joining portion 71 in the mold 70. When the resin temperature in the first extruder 68 is different from the resin temperature in the second extruder 69, it is preferable to mix a larger amount of heat stabilizer into the resin having a higher temperature in order to improve the thermal stability.

[0072] Next, the continuous pipe 77 extruded from the die 70 is introduced into the vacuum sizing device 63. The vacuum sizing device 63 is for shaping the outer surface of the continuous pipe 77 and cooling it. As shown in FIG. 5, the vacuum sizing device 63 has a main body 78 extending in the extrusion direction of the continuous pipe 77. An inlet 79 and an outlet 80 of the main body 78 are formed at one end and the other end in the longitudinal direction of the main body 78. A vacuum chamber 82 to which a vacuum pump 81 is connected is provided on the inlet 79 side in the main body 78. A sizing sleeve 83 is disposed in the vacuum chamber 82. One end of the sizing sleeve 83 is connected to the inlet 79. In addition, a cooling chamber 84 is provided between the vacuum chamber 82 and the outlet 80, and a water sprinkling pipe 85 is disposed over the entire length of the vacuum chamber 82 and the cooling chamber 84.

[0073] When the continuous pipe 77 is fed to the vacuum sizing device 63, the continuous pipe 77 expands due to the negative pressure of the vacuum pump 81, and its outer surface is brought into contact with the inner surface of the sizing sleeve 83, forming a shape, and the surface layer, inner layer and intermediate layer of the continuous pipe 77 are brought into contact with each other. The sized continuous pipe 77 is cooled and hardened by the cooling water sprayed from the water spray pipe 85. The inside of the vacuum sizing device 63 is preferably at a vacuum level of -1 KPa (gauge pressure) or less, more preferably at a vacuum level of -10 KPa (gauge pressure) or less, and even more preferably at a vacuum level of -20 KPa (gauge pressure) or less. If the vacuum level is equal to or less than the upper limit value, the pressure applied to the piping material in the thickness direction and circumferential direction increases, and the fusion strength between the intermediate layer and the inner layer and surface layer can be further increased. Instead of the vacuum sizing device 63, a cooling water tank in which cooling water is stored may be used, and a sizing sleeve may be provided at the inlet of the cooling water tank.

[0074] The take-up machine 64 is for taking up the continuous tube 77 at a constant speed. The take-up machine 64 is equipped with a plurality of take-up rollers 86 that are pressed against the lower and upper parts of the continuous tube 77. A motor (not shown) is connected to at least one of the take-up rollers 86, and the take-up speed of the continuous tube 77 is adjusted by controlling the number of rotations of the motor.

[0075] The cutter 65 is for cutting the continuous pipe 77 to a predetermined length. The cutter 65 is equipped with a sensor 87 that detects the tip position of the continuous pipe 77, and a cutting blade 88 that is driven in conjunction with the sensor 87. When the tip of the continuous pipe 77 presses the sensor 87, the cutting blade 88 is driven to cut the continuous pipe 77, and a piping material of a predetermined length is obtained.

[0076] (Installation examples and effects of piping structures) In the piping structure 1 of this embodiment, one receiving port 11a of the main pipe section 11 constituting the pipe fitting 10 is arranged inside the partition penetration section 2a, and the upper end of the first riser pipe 21 is connected to that receiving port 11a. In the piping structure 1 of this embodiment, the other socket 11b of the main pipe section 11 is disposed outside the compartment penetration section 2a and above the floor slab 2, and a lower end of the second standpipe 22 is connected to the socket 11b. In addition, the socket 12a of the horizontal branch pipe connection section 12 is disposed outside the compartment penetration section 2a and above the floor slab 2, and one end of the horizontal branch pipe 23 is connected to the socket 12a. The method of connecting each of the sockets 11a, 11b, 12a and each of the pipes 21, 22, 23 is not particularly limited, and a known method can be appropriately applied. A packing provided inside each socket can be used to seal the gap between the outer surface of each pipe and the inner surface of each socket, or an adhesive can be applied to the outer surface of each pipe to connect the inner surface of each socket and the outer surface of each pipe so that the inner surface of each socket and the outer surface of each pipe are sealed. When using an adhesive to join, a colored adhesive to which a coloring agent has been added, or an adhesive to which a luminescent agent that emits fluorescence or phosphorescence when exposed to ultraviolet light has been added can be used. However, the socket 11a and the pipe 21 located inside the partition penetration part 2a must be connected to each other with an adhesive so that the pipe 21 does not fall off the socket 11a even when the pipe 21 is heated and thermally expanded. The outer surfaces of the ends of the pipes 21, 22, 23 inserted into the sockets 11a, 11b, 12a of the pipe fitting 10 are tapered over the entire circumference. The tapered surface referred to here may be a shape in which the end 20a of the piping material 20 along the pipe axis is cut by a straight line, as shown in Fig. 6(a), for example. The end 20a of the piping material 20 may also be a shape in which the end 20a of the piping material 20 is cut by a circular arc, as shown in Fig. 6(b), for example. Figs. 6(a) and (b) are partial cross-sectional views of the end 20a of the piping material 20 having a three-layer structure of an inner layer 26, an intermediate layer 27, and a surface layer 28. When the pipes 21, 22, 23 have a three-layer structure of an inner layer, an intermediate layer, and a surface layer, and the intermediate layer is made of the resin composition (B), when the pipes 21, 22, 23 are inserted into the pipe fitting 10, the surface layer may be cut until the intermediate layer is exposed, or may be cut to such an extent that the intermediate layer is not exposed. If the intermediate layer is exposed, and the pipe fitting 10 is transparent, the intermediate layer of the exposed end face of the piping material 20 is black, so that the position of the end face can be visually confirmed from the outside, and it can be visually confirmed whether or not it is inserted to the back of the receiving port. In particular, when the fitting is transparent, the packing provided at the receiving port can be visually confirmed from the outside, so that it can be determined whether the end of the piping material 20 is inserted a predetermined length beyond the packing. If the intermediate layer is not exposed, the adhesive component does not penetrate into the intermediate layer or the interface between the intermediate layer and the surface layer, and the adhesive component can prevent interfacial peeling or cracking between the surface layer and the intermediate layer, and the adhesive component can be prevented from deteriorating due to the acidic thermally expandable graphite.

[0077] As described above, the piping material 20 used in the piping structure 1 of this embodiment contains thermally expandable graphite that expands when heated by a fire. For example, as shown in Fig. 7, when a fire occurs on a floor below the floor slab 2, the heat of the fire can cause the portion of the first standpipe 21 inside the compartment penetration portion 2a to expand and close the compartment penetration portion 2a. This can prevent flames, heat, and smoke from rising to a floor above the floor slab 2 through the compartment penetration portion 2a, thereby exhibiting fire resistance.

[0078] The piping material 20 of the present embodiment has an intermediate layer (fire-resistant layer) containing thermally expandable graphite with a specific aspect ratio, which provides good fire resistance, enhances compressive strength, and reduces thermal conductivity.

[0079] In a building, a floor material 4 for a living area is usually installed separately above a floor slab 2 that divides adjacent upper and lower floors. A space S is formed between the floor slab 2 and the floor material 4, and the horizontal branch pipe 23 is arranged in this space S. Therefore, the installation space for the horizontal branch pipe 23 is limited, but usually, in order to improve drainage, the horizontal branch pipe 23 is inclined so as to gradually become higher as it moves away from the socket 12a of the horizontal branch pipe connection part 12. For this reason, in the pipe joint 10, it is required to make the horizontal branch pipe connection part 12 as close to the floor slab 2 as possible, make the connection position of the horizontal branch pipe 23 as low as possible, and increase the degree of freedom of arrangement of the horizontal branch pipe 23 in the space S. In particular, when the building is an apartment building and there are many rooms on the same floor, the horizontal branch pipe 23 becomes long, but in that case, the position of the end of the horizontal branch pipe 23 opposite the horizontal branch pipe connection part 12 side becomes high. Therefore, it is required to utilize the space between the floor slab 2 and the floor material 4 as effectively as possible. For this reason, in the pipe joint 10, it is preferable to insert the main pipe section 11 as deeply as possible into the compartment penetration section 2a, and to bring the horizontal branch pipe connection section 12 close to the floor slab 2, and to connect the horizontal branch pipe 23 at a position as low as possible. Also, it is preferable that at least the upper end of the receiving port 11a does not exceed the upper surface of the floor slab 2, that is, the upper end of the standpipe 21 does not exceed the upper surface of the floor slab 2. In this case, the piping material 20 protrudes downward from the floor slab 2.

[0080] (Other embodiments) The present invention is not limited to the above embodiment. In the present invention, the piping material may have a socket at one end. In this case, the pipe joint has a spigot that is inserted into the socket of the piping material, and the spigot of the pipe joint is inserted into the socket of the piping material to form a piping structure. In addition, the piping material of the above-mentioned embodiment has a three-layer structure, but the piping material of the present invention only needs to have an intermediate layer (fire-resistant layer). The piping material of the present invention may have a single-layer structure consisting of only an intermediate layer, or a two-layer structure having only one of an inner layer and a surface layer. The piping material of the present invention is preferably a multi-layer structure having an intermediate layer and at least one of an inner layer and a surface layer. Alternatively, the piping material may have at least one of the surface layer and the inner layer being a fire-resistant layer (that is, a layer containing thermally expandable graphite), and the intermediate layer being a layer not containing thermally expandable graphite.

[0081] For example, in the present invention, it is not necessary for the pipe joint and the upper end of the first riser pipe to be connected with the lower surface of the lower socket of the pipe joint being flush with the lower surface of the floor slab. In other words, it is sufficient for the lower socket of the pipe joint and the upper end of the first riser pipe to be connected at any part within the compartment penetration part. In the present invention, the pipe joint is not limited to the three-way pipe joint of the shape described in the above embodiment, and may be a T-shaped pipe joint in which a side branch pipe connection part is provided perpendicular to a main pipe part of the pipe joint. In addition, the pipe joint may connect two standpipes and two or more side branch pipes, or may connect one standpipe and two or more side branch pipes. In the piping material, it is sufficient that at least the riser pipe is made of the resin composition (B), and the lateral branch pipe may be made of a resin composition other than the resin composition (B), i.e., a resin composition that does not contain thermally expandable graphite. Furthermore, the piping structure of the present invention may be one that is passed through a compartment penetration part formed in a wall. When the piping structure is one that is passed through a compartment penetration part formed in a wall, the pipe joint may be one that is provided with two sockets or one that is provided with three or more sockets. The piping structure of the present invention can also be used for a water supply line.

[0082] Furthermore, non-thermally expandable graphite may be added to the resin composition (A) to impart fire resistance. As the non-thermally expandable graphite, the one described in Japanese Patent No. 4829847 can be used, and by using non-thermally expandable graphite having a particle size of 10 μm or more and 1000 μm or less, preferably 10 μm or more and 100 μm or less, a translucent or transparent joint can be obtained.

[0083] Furthermore, the piping structure of the present invention may be in a state where the piping material and the pipe joint are previously joined with an adhesive in a factory or the like (so-called drainage manifold joint). In this case, the piping structure 1 includes an upper pipe joint 10a, a lower pipe joint 10b, and a piping material 20, as shown in FIG. The upper pipe fitting 10a has a receiving port 13a to which a piping material 20 can be connected, a receiving port 11b to which a second standpipe pipe 122 extending from the upper floor can be connected, and a receiving port 12a to which a horizontal branch pipe pipe 123 extending from the upper floor can be connected. The lower pipe fitting 10b has a socket 13b to which the piping material 20 can be connected, and a socket 11a to which a first standpipe 121 extending from the lower floor can be connected. The upper pipe joint 10a and the lower pipe joint 10b may be made of the resin composition (A) or may be made of a resin other than the resin composition (A). For example, the upper pipe joint 10a and the lower pipe joint 10b may be made of a polyvinyl chloride resin that does not contain a flame retardant. An upper end of the piping material 20 is connected to the socket 13a of the upper pipe joint 10a, and a lower end of the piping material 20 is connected to the socket 13b of the lower pipe joint 10b. The piping material 20 is composed of the resin composition (B). The resin contained in the resin composition (B) may be the same as or different from the resin contained in the resin composition (A). For example, when the resin composition (A) contains a polyvinyl chloride resin, the resin composition (B) may contain a polyethylene resin. In addition to drainage water from the second standpipe 122 extending from the upper floor, drainage water also flows from the side branch pipe 123 into the piping material 20. For this reason, the nominal diameter of the piping material 20 is set to be equal to or larger than the nominal diameters of the standpipe 122 and the side branch pipe 123. The general sizes of the standpipe 122 and the side branch pipe 123 are at most about nominal diameter 125, and in order to increase the degree of freedom in installation while limiting the variety of the piping structure 1, it is preferable that the piping material 20 has a nominal diameter of 125 or more, and preferably a nominal diameter of 200 or less. The first rise pipe 121, the second rise pipe 122, and the side branch pipe 123 may be made of the resin composition (A), may be made of the resin composition (B), or may be made of a material other than the resin composition (A) and the resin composition (B). However, when made of resin, the linear expansion coefficient is larger than when made of metal, and the amount of expansion and contraction due to heat is large, and stress is likely to concentrate at the contact points between the piping material 20 described later and the upper and lower surfaces of the mortar 3. The piping structure 1 shown in Fig. 8 is installed in a building such that the piping material 20 is disposed in the compartment penetration portion 2a of the floor slab 2. In this embodiment, the piping material 20 protrudes downward from the floor slab 2. Mortar 3 is filled between the piping structure 1 and the inner surface of the compartment penetration portion 2a, filling the gap between the inner surface of the compartment penetration portion 2a and the piping material 20 and fixing the piping structure 1. In this case, the piping material 20 protrudes downward from the floor slab 2. In this embodiment, when the riser pipe 121 thermally shrinks or a physical force is applied to the riser pipe 121 during construction, stress is concentrated at a contact point P between the piping material 20 and the lower surface of the mortar 3. The piping material 20 of the present invention has a high compression ratio, and therefore is not easily damaged even if stress is concentrated at the contact point P.

[0084] 9, the socket 13b of the lower pipe fitting 10b and the piping material 20 may be connected within the compartment penetration portion 2a of the floor slab 2. In this embodiment, the piping material 20 protrudes upward from the floor slab 2. In this embodiment, when the riser pipe 122 and the side branch pipe 123 are thermally contracted or when a physical force is applied to the riser pipe 122 and the side branch pipe 123 during construction, stress is concentrated at the contact point P1 between the piping material 20 and the upper surface of the mortar 3. The piping material 20 of the present invention has a high compression ratio and is therefore not easily damaged even if stress is concentrated at the contact point P1.

[0085] The socket 13b of the lower pipe fitting 10b and the piping material 20 may be connected within the compartment penetration portion 2a of the floor slab 2, respectively. Furthermore, both the socket 13b of the lower pipe fitting 10b and the socket 13a of the upper pipe fitting 10a may be connected to the piping material 20 within the compartment penetration portion 2a of the floor slab 2. In particular, when the compression ratio of the piping material 20 is 50% or less, it is preferable that both the socket 13b of the lower pipe fitting 10b and the socket 13a of the upper pipe fitting 10a are connected to the piping material 20 within the compartment penetration portion 2a of the floor slab 2. EXAMPLES

[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. (Raw materials used for piping materials) Thermally expandable graphite I: Air Water Inc., MZ-260, expansion start temperature 260°C or higher, average aspect ratio 25.3. Thermally expandable graphite II: Tosoh Corporation, GREP-EG, expansion start temperature 220℃, average aspect ratio 18. -Thermal expandable graphite III: Nippon Graphite Industry Co., Ltd., EXP50T, average aspect ratio 31. Thermally expandable graphite IV: Tosoh Corporation, GREP-EG (passed through 150 mesh), expansion start temperature 220°C, average aspect ratio 1.3. Thermally expandable graphite V: Tosoh Corporation, GREP-EG (did not pass through 5 mesh), expansion start temperature 220°C, average aspect ratio 45. -Polyvinyl chloride resin: TH1000, manufactured by Taiyo PVC Co., Ltd. Polyethylene resin: Suntech B770, manufactured by Asahi Kasei Corporation. Lead-based stabilizer: Sakai Chemical Industry Co., Ltd., SL-1000. Polyethylene-based lubricant: Hiwax 4202E, manufactured by Mitsui Chemicals, Inc. Flame retardant (aluminum hydroxide): Showa Denko H-31, average particle size 18 μm. Flame retardant (zinc phosphate): ZPO-3, manufactured by Suzuhiro Chemical Co., Ltd.

[0087] (Examples 1 to 6, 9, 10, 12 to 14, Comparative Examples 1 to 5) The piping material was composed of a surface layer, a middle layer which was a fire-resistant layer, and an inner layer. The resin composition constituting the intermediate layer was obtained as follows. According to the composition of the fire-resistant layer in Tables 1 to 3, polyvinyl chloride resin, thermally expandable graphite, a lead-based stabilizer, a polyethylene-based lubricant, and aluminum hydroxide were mixed, and then the mixture was stirred and mixed in a Henschel mixer (manufactured by Kawada Industries Co., Ltd.) having an internal volume of 200 liters to obtain a resin composition (B-1). The resin compositions constituting the surface layer and the inner layer were obtained as follows. 100 parts by mass of polyvinyl chloride resin (TH1000 manufactured by Taiyo PVC Co., Ltd.) was blended with 2 parts by mass of a tin-based stabilizer (product name "STX-80" manufactured by Daikyo Chemical Industry Co., Ltd.), 0.5 parts by mass of a polyethylene-based lubricant (Hiwax 4202E manufactured by Mitsui Chemicals, Inc.), and 3 parts by mass of calcium carbonate (Whiten SB manufactured by Shiraishi Calcium Co., Ltd.), and the mixture was stirred and mixed in a 200-liter Henschel mixer (manufactured by Kawada Industries Co., Ltd.) to obtain a resin composition (B-2). Using the manufacturing apparatus shown in FIG. 2, the resin composition (B-2) was supplied to a hopper 66 of a first extruder 61, and the resin composition (B-1) was supplied to a hopper 67 of a second extruder 62. The resin temperatures in the first extruder 68 and the second extruder 69 were set to 180° C., and each resin was supplied from the first extruder 68 and the second extruder 69 to a mold 70. The molding temperature in the mold 70 was set to 190° C., and the resins were extruded into a tubular shape to produce a piping material having an outer diameter of 216 mm, a surface layer and an inner layer each having a thickness of 2.0 mm, which were made of the resin composition (B-2), and an intermediate layer having a thickness of 8.0 mm, which was made of the resin composition (B-1) and was formed between the surface layer and the inner layer. In the obtained piping material, the positional relationship between the weld line in the middle layer and the weld lines in the inner layer and surface layer was the same as that shown in FIG. 4(g). The obtained piping materials were evaluated for thermal conductivity, thermal resistance, fusion strength, compression ratio, and fire resistance. The results are shown in Table 1. In the following, the fusion strength was evaluated only when the obtained piping materials were multi-layered.

[0088] Example 7 A piping material was produced in the same manner as in Example 1, except that the surface layer and the inner layer were not provided (that is, a single-layer structure consisting of only the fire-resistant layer was used). The resulting piping material was evaluated for thermal conductivity, thermal resistance, compressibility and fire resistance, and the results are shown in the table.

[0089] Comparative Example 6 Except for changing the composition of the fire-resistant layer as shown in Table 3, a piping material having a single-layer structure including only a fire-resistant layer was produced in the same manner as in Example 7. The obtained piping material was evaluated for thermal conductivity, thermal resistance, compressibility, and fire resistance, and the results are shown in the table.

[0090] Example 8 A piping material was produced in the same manner as in Example 1, except that the weld line in the intermediate layer and the weld lines in the inner layer and surface layer were formed in the same position. The obtained piping material was evaluated for thermal conductivity, thermal resistance, fusion strength, compressibility, and fire resistance, and the results are shown in the table.

[0091] Example 11 Except for changing the composition of the fire-resistant layer as shown in Table 2, a piping material having a single-layer structure including only a fire-resistant layer was produced in the same manner as in Example 7. The obtained piping material was evaluated for thermal conductivity, thermal resistance, compressibility, and fire resistance, and the results are shown in the table.

[0092] (Measurement method) [Fusion strength] A universal testing machine 50 shown in Fig. 10 was prepared. The universal testing machine 50 includes a random punching jig 51 and two compression plates (not shown). The random punching jig 51 includes a base portion 51a and a pressing portion 51b arranged above the base portion 51a. The random punching jig 51 is sandwiched between the two compression plates (not shown). Next, the piping material was cut into a tube having a width of 20 mm in the axial direction to prepare a test piece 25. The test piece 25 has an inner layer 26, an intermediate layer 27, and a surface layer (not shown). Under conditions of a temperature of 23°C±2°C and normal humidity (45-85%), the test piece 25 was set between the base portion 51a and the pressing portion 51b of the universal testing machine 50, and the test piece 25 was compressed in the direction of the tube axis at a speed of 10 mm / min±2 mm / min per minute using two compression plates. The maximum load at which the fused surfaces of the inner layer 26 and the intermediate layer 27 peeled off was determined, and the fusion strength was calculated using the following formulas (1) and (2). F = W / S (1) S = 3.14 × d × L (2) [In the formulas (1) and (2), F is the fusion strength (MPa), W is the maximum load (N), and S is the fusion area (cm 2 ), d is the average outer diameter of the inner layer 26 (cm), and L is the length of the test piece in the tube axial direction (cm).

[0093] [Fire resistance rating] A fire resistance test furnace 100 shown in FIG. 11 was prepared. The fire resistance test furnace 100 includes a heating chamber 110 sealed except for the upper part, a test floor slab 120 installed on the heating chamber 110, a burner 130 installed in the heating chamber 110 to generate a flame, and a thermocouple 140 for measuring the temperature in the heating chamber 110. A 100 mm thick PC (precast concrete) panel with a compartment penetration part 120a having a diameter of 260 mm was used as the floor slab 120. The thermocouple 140 was arranged so that the temperature near the lower end of the piping material 20 (first standpipe 21) in the heating chamber 110 could be measured. In addition, mortar 3 was filled between the pipe joint 10 and the inner surface of the compartment penetration part 120a to seal the compartment penetration part 120a. In this fire resistance test furnace 100, the piping structure 1 was installed in the same arrangement as in the above embodiment, using the pipe fitting 10 prepared as described above and pipes 21, 22, and 23 (piping material 20) prepared by cutting the piping materials of each embodiment and comparative example. Then, a fire resistance test (based on the evaluation method for fire resistance performance tests of the revised Building Standards Act that came into effect on June 1, 2000, and in accordance with ISO834-1) was conducted. In this fire resistance test, the time from the start of heating until smoke came out from the gap between the pipe joint 10 and the compartment penetration part 120a (smoke generation time) was measured. According to the criteria for the Fire Service Act, Section 8, if the smoke generation time was 120 minutes or more, it was deemed to be fire resistant, and if it was less than 120 minutes, it was deemed to be non-fire resistant. When the fire resistance test was carried out on the piping structure of Example 1, even after 120 minutes had elapsed since the start of heating, no smoke escaped from between the pipe fitting 10 and the compartment penetration portion 120a, demonstrating that the piping structure had fire resistance.

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097] As shown in Tables 1 and 2, Examples 1 to 14 had a compression ratio of 20% or more, and were therefore resistant to breakage, and had a fire resistance of 120 minutes or more, indicating excellent fire resistance. As shown in Table 3, Comparative Example 1, in which the content of thermally expandable graphite was 1 part by mass, and Comparative Example 3, in which spherical graphite was used, had a fire resistance of 90 minutes or less. Comparative Examples 2 and 4 to 6, in which the compression ratio was 5 to 19%, had insufficient strength. From the above, it has been found that application of the present invention makes it possible to provide piping materials with excellent fire resistance and resistance to breakage. [Explanation of symbols]

[0098] 1 Piping structure 2. Floor slab 2a Compartment penetration 3. Mortar 4. Flooring 10 Pipe fittings 10a Upper pipe joint 10b Lower pipe joint 11 Main Pipe Section 11a,11b socket 12 Horizontal branch pipe connection 12a socket 13a,13b socket 20 Piping materials 21 First standpipe (piping material) 22 Second standpipe (piping material) 23 Horizontal branch pipe (piping material) O1 tube shaft

Claims

1. A tubular peripheral wall is provided, The peripheral wall has a tubular fireproof layer containing 100 parts by mass of a thermoplastic resin and 4 parts by mass or more and less than 10 parts by mass of thermally expandable graphite, The outer diameter is 165 mm or more and 318 mm or less, The compression ratio measured by the following measurement method is 20% or more, The average aspect ratio of the thermally expandable graphite is 10 or more and 35 or less. <Measurement method> A ring-shaped test piece of 50 mm or more is cut from the piping material and left at 23° C. for 1 hour, after which the outer diameter of the pipe is compressed at a speed of 10 mm / min in the direction perpendicular to the pipe axis by sandwiching it between two flat plates. The degree of radial compression at the time of fracture of the three annular test pieces is measured, and the average value is regarded as the compression ratio.

2. A tubular peripheral wall is provided, The peripheral wall has a tubular fireproof layer containing 100 parts by mass of a thermoplastic resin and 4 parts by mass or more and less than 10 parts by mass of thermally expandable graphite, The outer diameter is 76 mm or more and 140 mm or less, The thickness of the fire-resistant layer is 70% or less of the thickness of the peripheral wall, The compression ratio measured by the following measurement method is 20% or more, The average aspect ratio of the thermally expandable graphite is 10 or more and 35 or less. <Measurement method> A ring-shaped test piece of 50 mm or more is cut from the piping material and left at 23° C. for 1 hour, after which the outer diameter of the pipe is compressed at a speed of 10 mm / min in the direction perpendicular to the pipe axis by sandwiching it between two flat plates. The degree of radial compression at the time of fracture of the three annular test pieces is measured, and the average value is regarded as the compression ratio.

3. The piping material according to claim 1 , further comprising a coating layer located on at least one of an inner circumferential surface and an outer circumferential surface of the fire-resistant layer, the coating layer covering the fire-resistant layer.

4. The piping material according to claim 3 , wherein a fusion strength between the fire-resistant layer and the coating layer is 1.5 MPa or more.

5. The fire-resistant layer has a weld line extending in the tube axial direction. Item 3. Piping material.

6. The thermal conductivity of the peripheral wall is 0.3 W / m·K or less. Piping materials listed.

7. The piping material according to any one of claims 1 to 6, wherein the fire-resistant layer contains a flame retardant.

8. A piping structure in which the piping material according to any one of claims 1 to 7, an upper pipe joint, and a lower pipe joint are pre-joined, The upper pipe joint has a connection portion that is connected to an upper end of the piping material, The lower pipe joint has a connection portion that is connected to a lower end of the piping material, A piping structure, in which, when the piping structure is installed, at least the piping material is positioned within a compartment penetration portion of a floor slab, and the piping material protrudes downward from the floor slab.

9. The method for producing a piping material according to claim 3 or 4, which has a multi-layer structure including at least a tubular fire-resistant layer and an inner coating layer located on the inner peripheral surface of the fire-resistant layer, The inner coating layer comprises a polyvinyl chloride resin, the fire-resistant layer includes a polyvinyl chloride resin and the thermally expandable graphite, The fire-resistant layer and the inner coating layer are laminated and extruded using an extrusion die, and then the laminate is introduced into a sizing sleeve to shape the outer surface.

Citation Information

Patent Citations

  • JP1974060806A

  • Fireproof three-layer pipe

    JP2001289363A

  • Multilayered fireproof pipe material

    JP2008180367A

  • Pipeline in building

    JP2009024411A

  • Waste water collecting joint

    JP2009057705A